The Role of Technology in Tranformation Human Resource Management: Systematic Literature Review - Muhammad Rafi Dhia (PT. Kreasi Karya Majakata, 2024)
This study aims to explore the impact of technology on the transformation of human resource management (HRM) through a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. Technology has profoundly influenced HRM in recent decades, affecting areas such as recruitment, training, performance management, and employee retention. The research identifies key trends, challenges, and the outcomes of technology implementation in HRM from 2016 to 2023. The goal is to provide valuable insights for practitioners and researchers to improve technology use in HRM and develop effective strategies to address existing challenges. Future research should focus on creating a comprehensive model and practical strategies for utilizing technology in HRM transformation.